THE EFFECT OF COMMUNICATION AND COORDINATION ON THE PERFORMANCE OF DAMKAR EMPLOYEES IN THE SATPOL PP OFFICE IN SERANG CITY - Fuadi, Fuadi; Munawaroh, Munawaroh; Siti Fatonah; Ilis Sulistiani (Jurnal Ekonomi, 2022)
This study was conducted to determine the effect of communication and coordination on the performance of employees in the fire department at the Serang City Satpol PP Service partially and simultaneously, with data collection techniques through questionnaires. The sampling technique used saturated sampling, the sample amounted to 74 people who were employees of the Fire Department of the Serang City Satpol PP Office. The descriptive analysis results showed that the respondents classified the communication, coordination and performance as very good because they were in the interval 4.20 – 5.00. By partial test the communication variable has a positive and significant effect on employee performance and the coordination variable has a significant and significant effect on employee performance in the Fire Department of the Satpol PP Serang City Office. In a joint test (simultaneous) communication and coordination have a positive and significant effect on the performance of the Fire Department of the Serang City Police Satpol PP employees. The percentage contribution of the influence of communication and coordination variables on employee performance variables is 43.4%, while the remaining 56.6% can be explained by other factors not examined in this study,